LEXICAL CLASSIFICATION OF BATIK MOJOKERTO MOTIFS (AN ETHNOSEMANTIC APPROACH) - NURFARIDA, IKA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: lexical classification, culture, ethnosemantics, batik Mojokerto         Language and culture is unity in a society. The bridge for studying culture and language is ethnolinguistics. In this study the writer focuses more on ethnosemanticapproach to analyze the names of Batik Mojokerto motifs. This research tries to answer the problems of study i.e: 1). what are the lexical units of motif of Batik Mojokerto? 2). What are the references of the name of Batik Mojokerto? 3). What are the relationship between the names of batik and socio – cultural values of Mojokertosociety?.Qualitative approach and interview are research design in this research. Interview is used to gain the information. The data is taken from informant who is maker of Batik Mojokerto and supporting data of the description of Batik Mojokerto from office of Dinas Koperasi, Perindustrian dan Perdagangan Kota Mojokerto.This research reveals that there are 15 names of Batik Mojokerto motifs. In lexical classification there are 13 Noun Phrases, 1 Verb Phrase, and 1 Adjective Phrase. Besides, there are distinctive names of the motif which comprise animal reference, that is Sisik, plant reference there are Mrico, Koro, and Talas, then the nature elements of Alas, Kali, Surya, and Bulan. There are 7 batik motif names which areinfluenced by socio – cultural values of Mojokerto society. The names are: MricoBolong, Sisik Gringsing, Mahkota Majapahit, Teratai Surya Majapahit, Surya Majapahit, Satrio Manah, and Gerbang Mahkota Raja. There are 5 batik names which refer to nature. The names are Bunga Matahari, Daun Talas, Koro Renteng, TerangBulan and Lerek Kali. The last background is influenced by human lifestyle, are: NamKloso, Rawan Inggek, and Alas Mojopahit.The writer expects the result of the research will be useful for the readers who are interested in the similar topic. The writer suggests the next researcher to conduct a similar research about relationship between language and culture to deeper analysis in socio–cultural contexts.